OPTIMIZATION ANALYSIS OF SALT FARMERS ACTIVITIES AND WELFARE IN PAMEKASAN REGENCY - Moh. Holis; Sayyidi Sayyidi; Musoffan Musoffan (EAJ (Economic and Accounting Journal), 2019)
Many salt farmers who are not eager to produce salt even many farmers are switching professions. This is due to the low price of local salt and the quality is even lower the quality of imported salt is even better so that it can reduce the bargaining power of local salt and consequently the salt farmers lose. This study aims to analyze the economic activities of salt farmers in Pamekasan Regency in order to evaluate the optimization of salt farmers' activities through internal and external factors, so that a development strategy can be designed to optimize the activity of salt farmers in order to support the welfare of salt farmers in Pamekasan. Using qualitative descriptive analysis, IFE and EFE matrix analysis and qualitative SWOT analysis. Based on the results of the study it can be concluded that the level of optimization of the internal and external environmental analysis of economic activity and welfare of salt farmers in Pamekasan district is in quadrant I, which is aggressive, of course, all forms of activities will be optimal and welfare is achieved. The strategies that can be used as policies to increase the optimization of salt farmer activities in Pamekasan Regency are as follows 1) Expanding Salt market share, 2) Increasing productivity, the amount of quality salt production and the interest of Salt Farmers 3) Creating farmer groups 4). Increasing Competitiveness Potential 5). Cooperation with all parties.